Penerapan Model Discovery Learning Berbasis STEM pada Materi Sistem Gerak Untuk Meningkatkan Keterampilan Berpikir Kritis - Fadlina Fadlina; Wiwit Artika*; Khairil Khairil; Cut Nurmaliah; Abdullah Abdullah (Jurnal Pendidikan Sains Indonesia, 2021)
Implementation of learning in class 11th MAN 1 and MAN 2 Banda Aceh City Students only get information without going through discussion activities, students who are not brave enough to express ideas or ideas, so that students are not trained in using their critical thinking skills. This study aims to determine the improvement of students' critical thinking skills through the application of the STEM-based discovery learning model to the motion system concept. The research approach used is quantitative with the type of pre-experimental research. The research design used is the one-group pretest-postest design. The population was all of 11th grade students, amounting to 292 people. The sampling technique used was a total sampling. The sample in this study consisted of 292 students. The instruments in this research were pretest and posttest multiple choice questions with reasoned. Data analysis consisted of normality test, paired sample t-test at a significant level of 0.05 and n-gain. The results of the paired sample t-test obtained tcount 48 and value (ρ.001), so it was concluded that there were differences in critical thinking skills and learning outcomes of students before and after learning with the application of the STEM-based discovery learning model to the motion system concept. The results of the n-gain test using the Meltzer formula showed that the gain in critical thinking skills was 0.85, so there was an increase in critical thinking skills with a high category.